2018
DOI: 10.1007/s00784-018-2639-z
|View full text |Cite
|
Sign up to set email alerts
|

Metallic crown-induced occlusal trauma as a protocol to evaluate inflammatory response in temporomandibular joint and periodontal tissues of rats

Abstract: The standardization of an experimental occlusal interference model will allow us to understand the deleterious effect and mechanisms that affect the orofacial tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 34 publications
1
21
0
3
Order By: Relevance
“…We demonstrated that occlusal trauma increases the protein levels of TNF‐α and IL‐6 in gingival tissues. In a previous study, we reported that TNF‐α and IL‐1β were significantly higher when compared to the sham group 16 . These results confirmed the installed inflammatory reaction resulting from traumatic injury.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…We demonstrated that occlusal trauma increases the protein levels of TNF‐α and IL‐6 in gingival tissues. In a previous study, we reported that TNF‐α and IL‐1β were significantly higher when compared to the sham group 16 . These results confirmed the installed inflammatory reaction resulting from traumatic injury.…”
Section: Discussionsupporting
confidence: 75%
“…After 28 days of metal crown cementation, 16 the animals were euthanized. Samples from the gingival tissue surrounding the lower first molar were collected and homogenized individually in an appropriate buffer containing protease inhibitors (Ripa Lysis Buffer, Santa Cruz, Biotechnology, Dallas, TX) followed by centrifugation at 10,000 rpm for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro mechanical stress induced the mRNA expression levels of TNF‐α in PDL cells . It has been reported that traumatic occlusion induced the release of TNF‐α in rat model . In this study, glyburide might reduce bone resorption by suppressing the expression of TNF‐α and IL‐6.…”
Section: Discussionmentioning
confidence: 67%